Religions of the world - Morris, Scott Edward; Chelsea House Publishers (New York : Chelsea House Publishers, 1993)
Eighteen map spreads show the distribution of the major religions and faiths of the world.
Includes glossary and index.
Includes bibliographical references.
Keywords: Religions -- Maps for children; Religions -- Maps; Atlases